In praise of the strange virtue of people-smuggling - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2003)
Almost everyone is against people-smuggling. The refugee advocate excoriating the government for its mistreatment of asylum seekers, no less than the departmental official bemoaning the numbers of boat people landing on Australian shores, feels well-justified in insisting that, somehow, something must be done to put an end to this 'evil trade'. On the scale of virtue, the people smuggler appears barely a notch above (and for many, several notches below) the drug dealer, the child molester, or the gangster.